Deficiency of PDK1 in liver results in glucose intolerance, impairment of insulin-regulated gene expression and liver failure - Mora, Alfonso (Portland Press Ltd., 2005)
The liver plays an important role in insulin-regulated glucose homoeostasis. To study the function of the PDK1 (3-phosphoinositide-dependent protein kinase-1) signalling pathway in mediating insulin's actions in the liver, we employed CRE recombinase/loxP technology to generate L(liver)-PDK1(−/−) mice, which lack expression of PDK1 in hepatocytes and in which insulin failed to induce activation of PKB in liver. The L-PDK1(−/−) mice were not insulin-intolerant, possessed normal levels of blood glucose and insulin under normal feeding conditions, but were markedly glucose-intolerant when injected with glucose. The L-PDK1(−/−) mice also possessed 10-fold lower levels of hepatic glycogen compared with control littermates, and were unable to normalize their blood glucose levels within 2 h after injection of insulin. The glucose intolerance of the L-PDK1(−/−) mice may be due to an inability of glucose to suppress hepatic glucose output through the gluconeogenic pathway, since the mRNA encoding hepatic PEPCK (phosphoenolpyruvate carboxykinase), G6Pase (glucose-6-phosphatase) and SREBP1 (sterol-regulatory-element-binding protein 1), which regulate gluconeogenesis, are no longer controlled by feeding. Furthermore, three other insulin-controlled genes, namely IGFBP1 (insulin-like-growth-factor-binding protein-1), IRS2 (insulin receptor substrate 2) and glucokinase, were regulated abnormally by feeding in the liver of PDK1-deficient mice. Finally, the L-PDK1(−/−) mice died between 4–16 weeks of age due to liver failure. These results establish that the PDK1 signalling pathway plays an important role in regulating glucose homoeostasis and controlling expression of insulin-regulated genes. They suggest that a deficiency of the PDK1 pathway in the liver could contribute to development of diabetes, as well as to liver failure.